Land conservation financing - McQueen, Mike (Island Press, 2003)
The authors present important new information on state-of-the-art conservation financing, showcasing programs in states that have become the nation's leaders in open-space protection: California, Colorado, Florida, Illinois, Maryland, Massachusetts, Minnesota, and New Jersey. They look at key local land protection efforts by examining model programs in DeKalb County, Georgia; Douglas County, Colorado; Jacksonville, Florida; Lake County, Illinois; Lancaster County, Pennsylvania; Marin County, California; the St. Louis metro area in Missouri and Illinois, and on Cape Cod, Massachusetts